Persepsi pelajar cemerlang biologi terhadap kepentingan penggunaan visual melalui buku teks dalam pembelajaran biologi - Wan Hanim, bt Yahya @ Wan Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to explore the excellent students' perceptions on the importance of visual aids in the Biology textbooks in learning Biology as a subject in the selected secondary schools in the state of Sarawak, Malaysia. This study was carried out on eight informants who achieved excellent grades in their Biology paper that is grade A + and A in Siji/ Pelajaran Malaysia (SPM) 2014. The informants involved in this study are from three secondary schools. These schools are Sekolah Menengah Kebangsaan Matang Jaya, Sekolah Menengah Kebangsaan Tunku Abdul Rahman dan Sekolah Menengah Sains Kuching in Pada11Jan District in the state of Sarawak, Malaysia. This study employed a qualitative approach through case studies and open-ended questionnaires for data collection purposes. The findings of this study indicates that, the use of colourful illustrations in the Biology textbooks are very helpful in helping them in better understanding the lesson contents besides it can help them to enhance their interests in reading the textbooks. To teachers and students in secondary schools it is also hope that, the findings of this research paper is ofgreat help to them in supporting teaching and learning activities in the classrooms. To the Ministry ofEducation Malaysia, educators and future researchers it is hope that this research finding may prOVide useful information to them to further research in the related fie Ids.